Mapping the Hot Spots and Evolution Main Path of Whole-Body Vibration Training Since the 21st Century: A Bibliometric Analysis - Dong, Dan; Sun, Mingli; Xu, Dan; Han, Shuang; Cui, Liyuan; Cao, Shu; Yang, Ying; Xu, Shuang (Frontiers in Bioengineering and Biotechnology, 2022)
To evaluate the global scientific output of research on whole-body vibration training (WBVT) and explore the current status and trends in this field over the past decade using bibliometric methods, we retrieved the literature related to WBVT from 2000 to the present in the Web of Science Core Collection (WoSCC). We analyzed annual publications and time cited over time and the distribution of countries, organizations, productive authors, and source journals by the web of science online bibliometric analysis. We visualized the WBVT research trends and explored the influential organizations and authors through VOSviewer. Then we constructed a citation chronology map by HistCite to obtain the knowledge base of this field and made a citation primary path analysis by Pajek. Finally, we mined the hot spots of WBVT by BICOMB and gCLUTO. Overall, there were 1,629 publications included in this study between 2000 and 2022. The United States contributed the most publications in this field, and the country with the most active partnership was Spain. The University of Cologne ranked highest among organizations. Bernardo-Filho, Mario, from Universidade do Estado do Rio de Janeiro, ranked first among the top productive authors. Journal of Strength and Conditioning Research topped the list of journals with the most publications on WBVT by a wide margin. WBVT research field started from Rittweger's study on the acute physiological effects of WBVT in 2000, which was divided into two stages. The first stage focused on improving athletic ability, and the second stage gradually turned to the application in medicine. Keywords analysis showed the exercise rehabilitation of several aging chronic diseases was the research trend and hot spot of WBVT. The current study provided a time-based development and a global network hub of WBVT research, contributing to identifying core target diseases of WBVT and providing various insights for researchers in the future.